Acceptability of long-acting antiretroviral therapy among people living with HIV who use drugs in Vancouver, Canada: A qualitative study - Koharu Loulou Chayama; Cara Ng; Isabella Brohman; Manal Mansoor; Will Small; Morgan Philbin; Alexandra B. Collins; Ryan McNeil (PLoS ONE, 2025)
Background People living with HIV (PLHIV) who use drugs face overlapping social-structural inequities that contribute to suboptimal adherence to antiretroviral therapy (ART). Recent research suggests that long-acting antiretroviral therapy (LA-ART) can offer an important alternative to daily oral ART by mitigating adherence barriers, but this work has largely excluded PLHIV who use drugs. We, therefore, explored the acceptability of injectable and transdermal LA-ART among PLHIV who use drugs in Canada, which has no-cost universal access to oral ART. Greater understanding of PLHIV who use drugs’ perspectives on LA-ART will be essential to fully leverage treatment advances and maximize its individual- and population-level benefits. Methods From February 2019 to February 2020, we conducted in-depth interviews with 33 PLHIV who use drugs in Vancouver, Canada with suboptimal ART adherence (i.e., ≦  50%). Participants were recruited for interviews through a prospective cohort study. Interviews were audio-recorded, transcribed, and analyzed using inductive and deductive approaches. Results Our analysis identified key factors shaping LA-ART acceptability. First, LA-ART enthusiasm was highest among participants who were less satisfied with oral ART regimens due to pill burden or adverse side effects for oral ART and participants who struggled with daily adherence due substance use and social-structural factors (e.g., homelessness, incarceration). Moreover, participants who had physicians they trusted identified their physicians as credible sources of information on LA-ART, and indicated a desire for informed and shared decision-making regarding treatment changes. Finally, participants emphasized that there is no one-size-fits-all treatment approach for PLHIV who use drugs and highlighted the importance of access to a full range of available treatment options, including LA-ART. Conclusions There is potential for high LA-ART uptake among PLHIV who use drugs, particularly those who experience adherence barriers due to their substance use and structural vulnerability. While our findings are limited by the specific population and setting, they nevertheless underscore the need for efforts to ensure universal and equitable access to LA-ART.